Potential of Rhizopus delemar and Rhizopus microsporus as tempeh starters (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Hartanti AT, Kurniawan BC, Gunawan AW. 2024. Potential of Rhizopus delemar and Rhizopus microsporus as tempeh starters. Biodiversitas 25: 4208-4214. The biodiversity of tempeh-associated Rhizopus in Indonesia has decreased due to the widespread use of commercial starters. This study aimed to conserve three pure Rhizopus strains (Rhizopus delemar ATH 53, R. microsporus ATH 1 and ATH 24) of tempeh starters and optimize their use in tempeh production. Using rice flour and Rhizopus spores at 106/mL concentration, tempeh starters were made and stored for up to 12 weeks, maintaining spore viability at 106/g with 7-14% water content. Tempeh production experiments utilized three starter doses (0.1, 0.2, 0.3 g per 100 g soybeans) and three different incubation temperatures (27, 30, and 35°C), all of which successfully yielded tempeh. Sensory evaluations revealed that ATH 1 and ATH 53 starters were superior over ATH 24, which produced a distinct yellow tempeh that sporulated easily. It was also noted that 0.1 g of starter per 100 g of soybeans was sufficient for producing high-quality tempeh, offering an efficient use of starter. By successfully conserving these Rhizopus strains as viable tempeh starters for at least 12 weeks, results of present study demonstrate a promising approach to maintaining biodiversity in Indonesian tempeh production, paving the way for further exploration of traditional Rhizopus strains in tempeh making.
Keywords: Conserve, Rhizopus, soybean, starters, tempeh, temperature, viability